Biomarkers of atrial cardiopathy in patients with different pathogenetic subtypes of ischemic stroke - S. A. Mekhryakov; A. A. Kulesh; L. I. Syromyatnikova; К. V. Sobyanin (Неврология, нейропсихиатрия, психосоматика)
Studies of the biomarkers of atrial cardiopathy seem to be promising for identifying patients with cryptogenic stroke (CS), in which an intensive search for atrial fibrillation is indicated. Nevertheless, the diagnostic value of these markers and their threshold values require clarification.Objective: to present the characteristics of echocardiographic markers for atrial cardiopathy and the serum concentration of N-terminal pro-Btype natriuretic peptide (NT-proBNP) in embolic CS versus cardioembolic stroke (CES) and non-cardioembolic stroke (non-CES) to determine the threshold values of parameters with the highest sensitivity and specificity in differentiating CES and non-CES.Patients and methods. A total of 259 patients with ischemic stroke were examined. The standard examination additionally involved calculation of the parameters that reflected left atrial LA) function (LAF): LA emptying fraction (LAEF), and LA functional index (LAFI). The serum NT-proBNP concentration was also determined in 75 patients.Results and discussion. The patients with CES versus those with CS and non-CES were characterized by a considerable increase in LA diameter (4.3 [3.5; 4.5] cm vs 3.7 [3.4; 4.0] cm vs 3.7 [3.4; 3.9] cm; p=0.005 and p=0.009, respectively), LAVI (35.7 [30.5; 39.9] ml/m2 vs 28.5 [25.6; 34.6] ml/m2 vs 27.1 [24.5; 31.2] ml/m2 ; p< 0.001) and NT-proBNP level (559 [409; 1144] pg/ml vs 164 [65; 308] pg/ml vs 191 [63; 446] pg/ml; p=0.002 and p=0.019, respectively), as well as by a lower LAEF value [50.3 [48.5; 51.1]% vs 54.7 [51.6; 56.6]% vs 54.9 [52.5; 56.8]%; p< 0.001). The only parameter that showed significant differences between all the three groups (CES, CS, and nonCES) was LAFI (0.24 [0.2; 0.32] units vs 0.37 [0.3; 0.47] units vs 0.40 [0.34; 0.47] units; p<0.00 1), while maintaining the differences in the values for the two groups (CS and non-CES) (p=0.004). The following threshold values of biomarkers were obtained for CES and nonCES; these were a LA diameter of 41.5 mm (p< 0.001), a LAVI of 36.3 ml/m2 (p< 0.001), a LAEF of 51.8% (p< 0.001), a LAFI of 0.28 units (p< 0.001), and an NT-proBNP of 316 pg/ml (p< 0.001). Analysis of the ROC curves and the area under the curve (AUC) revealed that the most informative criteria for sensitivity and specificity were LAEF (79 and 88%, AUC 0.89), NT-proBNP (67 and 91%, AUC 0.89) and LAFI (93 and 72%, AUC 0.81).Conclusion. The CS group and non-CES one are comparable in the echocardiographic manifestations of atrial cardiopathy and in serum NTproBNP values. LAEF and NT-proBNP concentrations are promising biomarkers to classify CS patients into potential arterio- and cardioembolic types.